1998
DOI: 10.1128/jcm.36.1.118-122.1998
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Nocardia farcinica by Pulsed-Field Gel Electrophoresis Reveals an Endemic Strain as Source of Hospital Infections

Abstract: Severe postoperative wound infections caused by Nocardia farcinica were repeatedly observed in a German hospital surgical ward. A pulsed-field gel electrophoresis (PFGE) protocol was established to characterize the genetic relatedness of the bacterial isolates from these infections. All 18 isolates from postoperative infections that have occurred since 1985 belong to a common endemic genotype; organisms of this genotype were also detected in the air of two rooms of the department where these postoperative infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…Animal‐to‐human transmission has not been reported . While most patients develop sporadic infections, clusters of nosocomial infection have occurred, including among transplant recipients, with possible sources being construction, contaminated air or healthcare worker hands . However, these studies have often lacked strain testing with molecular methods to confirm the relationship between infections .…”
Section: Transmission and Infection Control Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal‐to‐human transmission has not been reported . While most patients develop sporadic infections, clusters of nosocomial infection have occurred, including among transplant recipients, with possible sources being construction, contaminated air or healthcare worker hands . However, these studies have often lacked strain testing with molecular methods to confirm the relationship between infections .…”
Section: Transmission and Infection Control Issuesmentioning
confidence: 99%
“…However, these studies have often lacked strain testing with molecular methods to confirm the relationship between infections . In some cases however, investigators have demonstrated common source environmental and person‐to‐person transmission in health care facilities by using ribotyping and pulsed‐field gel electrophoresis methods . Although there are no measures that effectively prevent inhalation, TMP‐SMX prophylaxis in high‐risk populations, as noted above, may reduce the incidence of the disease .…”
Section: Transmission and Infection Control Issuesmentioning
confidence: 99%
“…There have been reports of presumed nosocomial outbreaks of Nocardia infection, but these studies have often lacked strain testing with molecular methods to confirm the relationship between infections (4). In some cases however, investigators have demonstrated common source environmental and person-to-person transmission in health care facilities by using ribotying and pulsed-field gel electrophoresis methods (111,112). Although there has been no effective measure to prevent inhalation, TMP-SMX prophylaxis in high risk populations, as noted earlier, may reduce the incidence of the disease (31,70,108).…”
Section: Transmission and Infection Control Issuesmentioning
confidence: 99%
“…Agarose blocks were prepared as described by Blumel, Blumel, Yassin, Schmidt-Rotte & Schaal (1998) with modifications. The bacterial growth obtained on BHIA at 25°C for 1 week was inoculated into 2 mL saline in a sterilized test tube with 2 g of glass beads (2 mm diameter), and the tube shaken for 10 min by a KM shaker (Iwaki Sangyo, Tokyo, Japan) to disperse the bacteria.…”
Section: Bsfge Of N Seriolaementioning
confidence: 99%